Computational guidance using sparse Gauss-Hermite quadrature differential dynamic programming - He, Shaoming; Shin, Hyo-Sang; Tsourdos, Antonios (Elsevier, 2019)
This paper proposes a new computational guidance algorithm using differential dynamic programming and sparse Gauss-Hermite quadrature rule. By the application of sparse Gauss-Hermite quadrature rule, numerical differentiation in the calculation of Hessian matrices and gradients in differential dynamic programming is avoided. Based on the new differential dynamic programming approach developed, a three-dimensional computational algorithm is proposed to control the impact angle and impact time for an air-to-surface interceptor. Extensive numerical simulations are performed to show the effectiveness of the proposed approach.
Keywords: Computational guidance; Differential dynamic programming; Sparse Gauss-Hermite quadrature; Impact angle; Impact time